Remote Sensing and GIS-Based Landslide Hazard Zonation: A Case Study from Western Ghats, Kerala, India - Arunkumar K.S.; Mufeeda C.T, (CV. Truly Science Publishing, 2026)
Background: Landslides are among the most destructive natural hazards in the hilly regions of Kerala, causing severe environmental and socio-economic damage. Nilambur Taluk in Malappuram District, located along the Western Ghats, has experienced frequent landslide events, particularly during the extreme rainfall events of August 2018 and 2019. Aim: This study aims to delineate landslide hazard zones in Nilambur Taluk using a GIS-based weighted overlay approach to support risk reduction and spatial planning. Methods: A landslide hazard zonation (LHZ) map was developed using an inverse ranking-based weighted overlay method. Multiple thematic layers—including slope, rainfall distribution, lineament density, drainage density, slope aspect, geology, land use/land cover (LULC), NDVI, elevation, distance from drainage, distance from road networks, and soil—were derived from Survey of India (SoI) toposheets and 2019 Landsat imagery. These layers were integrated within a GIS environment (ArcGIS 10.1). Each parameter was assigned a relative weight based on its contribution to landslide susceptibility, while classes within each layer were ranked on a scale of 0–5. Conclusion: The resulting LHZ map classifies the study area into five hazard categories: stable (5.8%), moderately stable (32.3%), moderately unstable (39%), highly unstable (22%), and critical (0.92%). Validation through field observations and geospatial analysis confirms that high and critical hazard zones are strongly associated with intense rainfall, steep slopes, high lineament density, and active erosional processes. The generated hazard zonation map serves as an effective tool for landslide risk mitigation, informed land-use planning, and sustainable geo-environmental management in Nilambur Taluk.